Political connections and the process of going public: evidence from China - Bill B. Francis; Iftekhar Hasan; Xian Sun (Bank of Finland, 2009)
We examine how political connections impact the process of going public. Specifically, we test how political connections impact the pricing of newly offered shares, the magnitude of underpricing, and the fixed cost of going public. Based on experiences of the new public firms in the Chinese security markets and using multiple measures of political connections, we find robust evidence that issuing firms with political connections reap significant preferential benefits from going public. To be specific, we find that firms irrespective of ownership arrangements with greater political connections have higher offering prices, less underpricing, and lower fixed costs during the going-public process.
URN:NBN:fi:bof-20140807534
Keywords: 330